PENENTUAN NILAI SATURASI MAGNETIK BATUAN PERIDOTIT ASAL DESA AWANG BANGKAL BARAT KABUPATEN BANJAR KALIMANTAN SELATAN - Sudarningsih Sudarningsih; Simon Sadok Siregar; Wenny Habib Ghofallena (Jurnal Fisika FLUX, 2013)
Abstrak : Peridotite rocks are ultra-alkaline rocks that igneous rocks which highin mineral content of FeO, and also a magnetic mineral. Each rock type hasspecific properties and characteristics are manifested in the magnetic field inmagnetic parameters of rocks or minerals. One way to provide an overview of thecomposition and type of magnetic minerals in these rocks is to determine themagnetic saturation curve. Giving Isothermal Remanent Magnetism (IRM) isdone using instruments Electromagnetic Weiss gradually began to flow 1A, 2A,3A 10 A, etc., until the sample reaches saturation magnetic intensity. On themeasurement of magnetic saturation curve samples will be given a very largemagnetic field (until 0.8 T) gradually by using an electromagnet. The intensity ofmagnetization, as measured by Minispin magnetometer, and then plotted as afunction of the magnitude of a given field. The shape of this saturation curve willprovide an overview of the composition and type of magnetic minerals that existin the sample. The results showed that the shape of the IRM curve (remanentmagnetic intensity) is reached more quickly saturated the H <300 mT theperidotite rock in the identification of the mineral magnetite. The identification ofthese magnetic minerals is also based on the curvature of the IRM (remanentmagnetic intensity), the composition obtained is Fe3O4.Keywords: peridotite rocks, magnetic saturation, Isothermal RemanentMagnetism (IRM)